Maternal supplementation with uridine influences fatty acid and amino acid constituents of offspring in a sow–piglet model - Gao, Lu-min; Liu, Yi-lin; Zhou, Xihong; Zhang, Yan; Wu, Xin; Yin, Yu-long (British journal of nutrition, 2021)
To investigate the cumulative effects of maternal supplementation with nucleotides in the form of uridine (UR) on fatty acid and amino acid constituents of neonatal piglets, fifty-two sows in late gestation were assigned randomly into the control (CON) group (fed a basal diet) or UR group (fed a basal diet with 150 g/t UR). Samples of neonates were collected during farrowing. Results showed that supplementing with UR in sows’ diet significantly decreased the birth mortality of pigs (P = 0·05), and increased serum total cholesterol, HDL and LDL of neonatal piglets (P < 0·05). Moreover, the amino acid profile of serum and liver of neonatal piglets was affected by the addition of UR in sows’ diets (P < 0·05). Furthermore, an up-regulation of mRNA expression of energy metabolism-related genes, including fatty acid elongase 5, fatty acid desaturase 1, hormone-sensitive lipase and cholesterol-7a-hydroxylase, was observed in the liver of neonates from the UR group. Additionally, a decrease in placental gene expression of excitatory amino acid transporters 2, excitatory amino acid transporter 3 and neutral AA transporter 1 in the UR group was concurrently observed (P < 0·05), and higher protein expression of phosphorylated protein kinase B, raptor, PPARα and PPARγ in placenta from the UR group was also observed (P < 0·05). Together, these results showed that maternal UR supplementation could regulate placental nutrient transport, largely in response to an alteration of mTORC1–PPAR signalling, thus regulating the nutrition metabolism of neonatal piglets and improving reproductive performance.